Reactivity of the triple task on writing processes and product in adults with dyslexia - Olujić Tomazin, Marina; Kuvač Kraljević, Jelena; Alves, Rui A. (Frontiers in Psychology, 2023)
The triple task (TT) is a method for assessing (meta)cognitive processes and their dynamics during text writing. It involves three tasks in one: writing a text, responding quickly to a sound, and reporting the metacognitive process. Previous research has mostly shown that there is no interference between TT and measures of the writing process or writing product. However, individuals with dyslexia often show difficulties in tasks that require organization, automation, integration of multiple processes, inhibition, and shifting/cognitive flexibility. Therefore, the purpose of this study was to investigate whether TT affects the writing process and written product differently in adults with dyslexia than in a control group of adults with typical reading skills. Two groups of adult native Croatian speakers were included in this study: 20 adults with developmental dyslexia and 20 adults with typical reading skills. The groups differed in age (18 to 38 years), gender (13 males, 7 females per group), educational level, and nonverbal cognitive abilities. All participants wrote one text with a TT and another without. Text writing was tracked using a keystroke logging program - Inputlog - and text quality was assessed. The texts were compared in terms of several process variables, including process time, revisions, and fluency, and in terms of text quality, including productivity, syntactic complexity, lexical complexity, and accuracy. The results showed that measures of writing processes and text quality in the group of adults with dyslexia and the group of adults with typical reading skills were probably not differentially affected by TT. However, in the no TT condition, the total number of characters per minute was higher, more keys were typed per minute and more words were deleted. As expected, adults with dyslexia produced shorter texts of lower quality and with more errors; they also produced fewer characters per minute, used fewer keystrokes, and typed fewer.